Code name Sapphire - Jenoff, Pam (Park Row Books, 2023)
"Hannah Martel has narrowly escaped Nazi Germany after her fiancé was killed in a pogrom. When her ship bound for America is turned away at port, she has nowhere to go but to her cousin Lily, who lives with her family in Brussels. Fearful for her life, Hannah is desperate to get out of occupied Europe. But with no safe way to leave, she must return to the dangerous underground work she thought she had left behind"--